Sistema de seguridad industrial - Camacho Solórzano, Allan Omar (2009)
This work is to develop an industrial security system in the form of a didactic prototype, including its design, test and implementation. The system will be configurable, adaptable and scalable to different real industrial situations. This project is powered by LabVIEW 8.5 with IMAQ Vision libraries applied in the design of different applications. The system displays and controls remotely the entry and exit of personnel to certain industrial areas. Motion sensors are used to monitor events, registering date, time and an image of the activity detected in a database table. Besides the system controls ambient temperature that serves to activates alarms in the required cases. As hardware elements were used: LX16C motion sensor; One LM35 temperature sensor; webcams to catch and send images; a 18F4520 Microchip microcontroller that process the signals coming from the sensors and sets up the communication via Ethernet assisted by the module ET-MINI ENC28J60.